Training and Career Development Strategy: Improving Employee Competence and Performance at PT Nusantara Medika Utama: Strategi Pelatihan dan Pengembangan Karir: Meningkatkan Kompetensi dan Kinerja Karyawan Pada PT Nusantara Medika Utama - Zahra Sofia Rosa; Sulastri Irbayuni (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
PT Nusantara Medika Utama as a leading healthcare service provider, realizes the importance of developing quality human resources to achieve superior performance. In its annual report, the company emphasizes the focus on strengthening fundamentals through digitalization of healthcare services and improving staff competency by conducting various training and career development programs. This activity examines the training and career development strategies implemented by PT Nusantara Medika Utama. The results of the study show that structured and sustainable training programs are able to improve employees' technical and non-technical skills. Career development supported by management has created high work motivation and a harmonious work culture. Training and career development programs show benefits for various parties, such as officials, doctors, and also workers' children. The use of digital technology in training also facilitates access and efficiency of learning for employees. However, there is still a need to develop technology-based training programs, increase collaboration with external institutions, and conduct continuous evaluations to ensure program effectiveness.